Identification and characterisation of potential bacteriocins with biological activity against Clostridium difficile from environmental samples - Kim, Sungchan (2018)
Recently, the incidence of Clostridium difficile infection (CDI) has been decreasing but still presents a real threat as one of the common causes of nosocomial infection. It represents a real challenge in healthcare settings as one of the main causes of CDI is the use of commonly prescribed broad spectrum antibiotics. Effective infection control along with limiting the use of broad spectrum antibiotics can play their part in reducing CDI but fundamental need for an alternative to antibiotic treatment regime for CDI need to be addressed. Narrow spectrum, antimicrobial peptide bacteriocins can offer a viable alternative to antibiotics. This research was designed to isolate and identify novel bacterocins from environmental samples that are active against C. difficile by a screening of heat treated, and non-heat treated sewage and faecal samples. 12 environmental isolates were found to have an inhibitory effect on indicator strain C. difficile strain CD630 out of which 8 environmental isolates (S2, S3, S6, S7, S8, S9, S10 and S11) exhibited inhibitory effect on growth of at least 3 of 5 clinically relevant C. difficile strains such as EK28, CD630, DH196, DH478 and R20291. Greatest activity was observed on isolate S2 on all five C. difficile strains. Growth curve analysis of all environmental isolates active against C. difficile revealed that isolate S2 showed significantly slower growth rate compare to other isolates that had growth rates similar to or faster than CD630. Gram staining and 16s rRNA sequencing revealed most of the environmental isolates obtained active against C. difficile belonged to the Enterococcus group (S2, S3, S4, S6, S7 and S8) whereas others (S9, S10 and S11) were different species of Clostridium group. Other investigations to determine the identity of isolate S2 confirmed isolate S2 as Enterococcus. Whole genome sequencing of S2 was done to identify the exact species of Enterococcus S2. CSF or filtrate obtained from isolate S2 showed inhibition of the growth of CD630 in growing medium and increasing the percentage of the filtrate of isolate exhibited increased inhibition of the growth of CD630. Inhibitory effect of the filtrate of isolate S2 on indicator strain was proteases (proteinase K and trypsin) sensitive. The concentrated filtrate of isolate S2, when spotted on a lawn of CD630, exhibited the zone of inhibition of growth of CD630 as well as other strains whereas not concentrated CFS of isolate S2 didn't. CFS of isolate S2 was active on CD630 till critical dilution of 1 in 20ml. CFS of isolate S2 induced with hydrogen peroxide or co-culturing with different Enterococcus gave a more significant zone of clearance than that of Mitomycin C which is the well-known agent to induce a stress response that may increase the production of bacteriocin. The active ingredient in CFS of isolate S2 that gives a zone of clearance on CD630 is both effective in low and normal room temperature. However, the active component may be relatively unstable as its activity faded over a period of time. Concentrated CFS of isolate S2 did not have any zone of clearance when heat treated. SDS-PAGE analysis of CFS of isolate S2 has shown a presence of many protein molecules of size varying from 25-180 kDa from which active component of CFS of isolate S2 will need to be identified. Most of the experimental data obtained from this investigation provide a good indication of the potential production of protein-based antimicrobial substance like bacteriocin active against C. difficile from environmental isolate S2, but further experiments in future are of paramount importance to confirm potential bacteriocin from isolate S2 active against C. difficile and its possible potential as antimicrobial substance.